EFFECTS OF DIFFERENT LEG LOADINGS AT TAKE-OFF ON LANDING CHARACTERISTICS IN TWISTING SOMERSAULTS - Miha Marinšek; Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
The purpose of the study was to determine whether take-off asymmetry affects landing asymmetry. Eleven male gymnasts performed forward and backward somersaults with 1/2, 1/1, and 3/2 twists. The leading leg for each participant was defined according to the twisting direction. Ground reaction forces under each foot were measured with Parotec insoles. Absolute and relative measures of lateral asymmetry were used as dependent variables. Three-way ANOVA and a series of one-way ANOVAs were used to determine the main effects between take-off and landing. A series of paired t-tests with Bonferroni corrections were used to find differences between the leading and non-leading legs. Maximal ground reaction forces showed that the leading leg was set out to a higher load at take-off than the non-leading leg for twisting somersaults. There were no statistically significant differences found in the maximal ground reaction force between the legs at landings. Index of bilateral asymmetry indicated landings with negligible asymmetry. However, the maximal force differences between the legs in somersault 3/2 were higher when compared to other somersault variations. No evidence was found to affirm that the asymmetry at take-off affects asymmetry at landing in a twisting somersault. Presumably, gymnasts can take corrective measures during the aerial phase of the twisting somersault that effectively diminish the tilt of the body and enable gymnasts to prepare for the landing with small proportional asymmetry. Prudence is required as these proportions rise in the quantity of load with the height of the somersault.